An innovative surgical technique for subretinal transplantation of human embryonic stem cell-derived retinal pigmented epithelium in Yucatan mini pigs: preliminary results - Fernandes, Rodrigo Cardoso; Koss, Michael Janusz (Ophthalmic surgery, lasers & imaging retina, 2016)
Ophthalmic Surgery, Lasers and Imaging Retina | BACKGROUND AND OBJECTIVE: - To develop a safe and efficient surgical procedure for subretinal implantation into porcine eyes of a human embryonic stem cell-derived retinal pigmented epithelium (hESC-RPE) monolayer seeded onto a Parylene-C scaffold. This implant is referred to as CPCB-RPE1. - - MATERIALS AND METHODS: - Ultrathin Parylene-C scaffolds were seeded with hESC-RPE and surgically implanted into